From alternative to traditional an investigative study on party-list representation in the 15th Philippine Congress - Cayabyab, Marc Jayson De Vera (2012)
"The study investigated the party-list representation in the 15th Congress. By analyzing wealth indicators, it revealed that most of the representatives who are supposed to represent the marginal sectors are not marginalized themselves, defeating the purpose of the party-list system to open Congress to the marginalized and underrepresented. Party-list representatives are educated professionals with either a background in law or business. Most of the party-list representatives are also multi-millionaires. A number of them are even members of political dynasties who skirted around the party-list law. Representatives also failed to file bills - or have not filed any bills at all - that address the concerns of their sectors in Congress. Some have even "regionalized" their constituencies in order to easily win as party-list representatives, at the same time allocating their pork barrel to their bailiwicks as preparation for the next party-list elections. In the end, the flaws of the party-list system can be resolved by amending the party-list law. But the experience in Congress shows that amending the party-list law is slow and futile, especially when those who benefit from the vague law are sitting in Congress. The findings are contained in a four-part series written in a journalistic maner with a CD accompaniment."